The effect of explicit vocabulary teaching on vocabulary acquisition and attitude towards reading - Hasbún Hasbún, Leyla (Universidad de Costa Rica, 2005)
This study examines the effects of explicit vocabulary teaching on vocabulary acquisition and on attitude towards reading in an EFL class.  Vocabulary exercises following the Lexical Approach (Lewis, 1993, 1997, 2000) were designed to supplement a college reading comprehension course, and several reading strategies were systematically practiced.  Statistical analyses revealed that the students acquired the vocabulary.   In addition, at the end of the term, learners claimed that knowing more words had made them better readers, and the final evaluation of the course showed that their attitude towards reading had greatly improved. El presente trabajo investiga los efectos que produce la enseñanza explícita del vocabulario tanto en la adquisición de dicho vocabulario como en la actitud de un grupo de estudiantes de inglés como lengua extranjera hacia la lectura. Se diseñó un grupo de ejercicios siguiendo el Acercamiento Léxico (Lewis, 1993, 1997, 2000) para complementar un curso universitario de comprensión de lectura. Además, en forma sistemática, se utilizaron varias estrategias de lectura en clase. Los análisis estadísticos revelaron que los aprendices habían adquirido el vocabulario. Al finalizar el semestre, los estudiantes afirmaron que el conocimiento de nuevas palabras los había hecho mejores lectores, y la evaluación del curso reveló que la actitud de los estudiantes hacia la lectura había mejorado en forma significativa.